Sosialisasi Intoleransi sebagai Upaya Pencegahan Dosa Besar Pendidikan terhadap Siswa Siswi di Sekolah Dasar - Jamal, Andi Angraini; Yanis, Muhammad; Ahmad, Ahmad (Universitas Nusantara PGRI Kediri, 2025)
This service aims to improve understanding and measure the effectiveness of the intolerance socialization program in changing student attitudes and behavior at SD INPRES MOROWA. The method used is a qualitative method with a Focus discussion group (FGD) approach. The results showed a significant increase in student tolerance after participating in the program. In addition, fun and interactive learning methods, as well as the involvement of teachers and students, were found to play a major role in the success of this program. Therefore, this intolerance socialization proves that efforts to prevent major educational sins can be started early and have positive implications for the development of student character with This program also helps build student character by increasing awareness of the importance of diversity, reducing the possibility of social conflict, and strengthening the identity of a pluralistic nation. Students are also trained to foster critical attitudes and empathy, which are very important to face challenges around the world. And also able as an aspect to overcome global problems, especially to support the quality of quality education in accordance with what is one of the 17 goals of the world's sustainable program that has been agreed upon by the UN, namely the SDGs.